2019
DOI: 10.48550/arxiv.1908.01551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imperio: Robust Over-the-Air Adversarial Examples for Automatic Speech Recognition Systems

Abstract: Automatic speech recognition (ASR) systems are possible to fool via targeted adversarial examples. These can induce the ASR to produce arbitrary transcriptions in response to any type of audio signal, be it speech, environmental sounds, or music. However, in general, those adversarial examples did not work in a real-world setup, where the examples are played over the air but have to be fed into the ASR system directly. In some cases, where the adversarial examples could be successfully played over the air, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In this work, we propose VENOMAVE, the first clean-label data poisoning attack against ASR systems. Other than current adversarial attacks on ASR systems [8,24,25] which target the system during inference (i.e., the attacker creates malicious input that causes a misclassification), data poisoning attacks target the system during the training phase. Such poisoning attacks were already shown to be viable against image classification, but to the best of our knowledge, no data poisoning attack was yet proposed against ASR systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we propose VENOMAVE, the first clean-label data poisoning attack against ASR systems. Other than current adversarial attacks on ASR systems [8,24,25] which target the system during inference (i.e., the attacker creates malicious input that causes a misclassification), data poisoning attacks target the system during the training phase. Such poisoning attacks were already shown to be viable against image classification, but to the best of our knowledge, no data poisoning attack was yet proposed against ASR systems.…”
Section: Methodsmentioning
confidence: 99%
“…While ASR systems have become ever more reliable on clean data, they are still susceptible to malicious input, i.e. adversarial examples [2,8,24,25]. In these evasion attacks, a targeted audio file is perturbed by imperceptible amounts of adversarial noise at run time to trigger a misclassification of the victim's neural network.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Section II, transmission channel is a major concern when conducting physical attacks against ASR systems. During the past few years, many related works [5], [16], [20], [26], [28], [40], [65], [85], [95], [109], [134], [144] have emerged to enhance the robustness of the crafted audio adversarial examples in the physical space by exploiting transmission channel.…”
Section: A Targeting Transmission Channelmentioning
confidence: 99%
“…This is referred to as a targeted attack and such an adversarial audio waveform may be 99.9% similar to a benign sample (Carlini & Wagner, 2018). Also, recent work (Schönherr et al, 2019;Qin et al, 2019;Yakura & Sakuma, 2018) has demonstrated the feasibility of these adversarial samples being played over-the-air by simulating room impulse responses and making them robust to reverberations. We observe that the key differentiation between generating adversarial examples across different tasks or input modalities such as images, audio or text lies in a change of architecture as these attacks generally attempt to maximize the training loss and it is valuable to study properties of adversarial examples that hold across multiple domains.…”
Section: Introductionmentioning
confidence: 99%